Linguoculturemes in the rhetorical scheme of Ukrainian defensive speeches in Galicia in the beginning of 20th century - Zabolotna, Alina (Ukrainian linguistics, 2020)
The article is devoted to the analysis of functional mechanisms of persuasive speech formulas, namely, linguoculturemes (ethnic, cultural stereotypes, mythologemes, and precedent phenomena) in the defensive speeches of Ukrainian lawyers in Galicia in the beginning of 20th century. The purpose of the paper is to investigate the interaction between historical, political and sociocultural factors and strategies of linguoculturemes’ usage. The phenomenon of the rhetorical scheme is analyzed from the standpoint of extralinguistic context. The rhetorical scheme is considered as a set of rhetorical communicative instruments by which the speaker relays his own rhetorical picture of the world in order to influence the common socio-cultural communicative space. Linguoculturemes are described as essential media of historical, political, and cultural discourse in persuasive speeches. The main strategies of communicative formulas in defensive speeches of Ukrainian barristers of Galicia are analyzed. The strategy of selection of linguoculturemes was in keeping with the traditions of the Austro-Hungarian judiciary but also the desire to establish Ukrainian national identity. All precedent phenomena were used due to the imperial model of the world and achievements of the Polish people. However, at the beginning of the twentieth century, under the imperial regime, attempts to form a rhetorical scheme of defensive speeches focused on Ukrainian values and statehood can be noticed. The article considers the essence of defensive speech as an example of the official communication linked to social context in two ways: the extralinguistic conditions affect the speech structure, and the speaker, in turn, selects certain communicative formulas (linguoculturemes) to establish the linguocultural identity. The future tendencies of Ukrainian judicial rhetoric are the improvement of the communicative skills of the lawyers-rhetoricians, the rejection of Russian legal stamps, and the reactivation of traditional Ukrainian linguoculturemes. Information about the author: Alina Zabolotna – Student of the Institute of Philology, Taras Shevchenko National University of Kyiv (Ukraine). E-mail: oksanamatsko@ukr.net __________ References • Vorobev V. V. (1997). Linguoculturology (theory and methods). Moscow: Izd-vo Ros. un-ta druzhby narodov, 331 p. (in Russian). • Ryzhkov V. A. (1998). Peculiarities of stereotypization that are necessary accompanying the individual socialization within a certain national-cultural community. Yazyikovoe soznanie: Stereotipyi i tvorchestvo. Moscow: IJAZ, pp. 4–16 (in Russian). • Selivanova O. O. (2008). Modern linguistics: approaches and problems. Poltava: Dovkillia, 712 p. (in Ukrainian). • Hazagerov G. G. (2008). Rhetoric vs. stylistics: semiotic and institutional aspect. Sotsiologicheskiy zhurnal. Moscow: Institut sociologii FNISC RAN. no. 3, pp. 30–44 (in Russian). • Hazagerov G. G. (2016). Teleological sense and social role of the rhetorical figures’ classification. Vestnik Rossiyskogo universiteta druzhbyi narodov. Seriya: Lingvistika.Moscow: Izd-vo Ros. un-ta druzhby narodov, vol. 20. no. 3, pp. 89–102 (in Russian). • Lachmann R. (1994). Die Zerstörung der Schönen Rede. Rhetorische Tradition und Konzepte des Poetischen. Munchen: Wilhelm Fink (in German).